Total Body PET Imaging From Mice to Humans - Jones, Terry (Frontiers in Physics, 2020)
The technology of Total Body PET scanning has been recently established. To advance its application for undertaking across body research in humans, small animal PET scanning is positioned to undertake programs of the pre-clinical development of paradigms and protocols that would be translatable to human total body studies.